DESCRIPTION OF THE PUPA OF SCLEROSTOMUS CUCULLATUS (BLANCHARD, 1842) (COLEOPTERA: LUCANIDAE) (Acta Entomológica Chilena, 2022)
Pupa of the Sclerostomus cucullatus (Blanchard, 1842) is described on material collected at Lonquimay (Malleco, Chile).
Keywords: Coleóptera, Lucanidae, Sclerostomus cucullatus, morphology, pupa, Chile